The Co-Movement among Taiwan and International Stock Market - Chi, Ching-Hsin (2006)
This dissertation provides evidence to support the hypothesis that may support that there may be long-term benefits for the Taiwanese investors to diversify in the international equity market. The evidence is based on the data from the stock markets of the United States, Hong Kong and Japanese stock market over the period of 1st January 2001 to 31st December 2005. Time-series analytical techniques were used: Granger Causality test and the vector auto-regression (VAR) models. Analyses of Impulse Response and Variance Decomposition were adopted in order to examine the correlations between the Taiwanese stock market and the other national markets.